Analysis of routing protocols for software-defined vehicular ad hoc networks. (21st April 2021) - Patil, Annapurna P.; Hurali, Lalitha Chinmayee M.
With the rapid development of smart cities, intelligent transport systems (ITSs) have revolutionised the modern transportation system. Vehicular ad hoc networks (VANETs) have become the backbones of the ITS. These VANETs are characterised by high mobility and dynamically changing topology, leading to frequent link breaks. Thus, routing is an essential aspect of VANETs, contributing to the overall network performance. Some challenges regarding routing are diminished quality of service (QoS), heterogeneous networks, and security. These challenges are efficiently addressed by a networking paradigm called software define networking (SDN). In this paper, we present the current state of the art in SDN based routing along with its merits. Also, a novel taxonomy of such routing protocols based on the organisation of the SDN controller, QoS metric, security, heterogeneity, and type of communication is presented. We conclude the analysis with the benefits of SDN-based routing over the traditional network-based VANETs concerning QoS, security, and heterogeneity in the networks.